Investigating the Prevalence, Antibiotic Resistance Pattern, and Serotyping of Shigella Isolates from Traditional and Industrial Olivier Salads - Shiva Jahanbakhshi; Mohammad Mehdi Soltan Dallal; Abbas Rahimi Foroushani; Katayoun Samimi-Rad; Seyedeh Zohre Mirbagheri; Ahmad Nasser; Mohammad Reza Mohammadi (Journal of Nutrition and Food Security)
Background: Food-borne diseases are one of the major problems in developing countries. This study aims to investigate the prevalence, antibiotic resistance pattern, and serotyping of Shigella isolates from Olivier salad. Methods: 150 samples of Olivier salad, including 50 industrial samples from 10 different available brands in Tehran's shops and 100 traditional samples from Tehran's southern regions, were randomly obtained between April to October of 2021. These samples were examined for bacterial isolation and identification, which was finally confirmed by the API-20E kit. Then, a serological reaction was used to confirm Shigella and determine the species. The antibiotic resistance pattern of isolates was evaluated according to Clinical and Laboratory Standards Institute (CLSI, 2021) instructions by the Kirby-Bauer method. Results: Among these samples, 10 isolates (6.6%) of Shigella were isolated, of which 6 (4%) belonged to serogroup D (Shigella sonnei), 3 (2%) to serogroup B (Shigella flexneri), and 1 isolate (0.66%) belonged to serogroup C (Shigella boydii). This study showed that all Shigella isolates were related to traditional Olivier salad and were not Shigella spp. isolated from the industrial salad. Other bacteria isolated from traditional salad included Escherichia coli, Salmonella, Pseudomonas, Klebsiella, and Citrobacter. Multidrug resistance (MDR) was not observed in all isolates, and among 10 isolates of Shigella, 40%  showed complete resistance to ampicillin, but other isolates showed 60% intermediate resistance to this antibiotic. No resistance was observed for other tested antibiotics. Conclusion: The difference between the level of contamination in both traditional and industrial samples of salad well indicates familiarity with sanitary protocols and standards provided to reduce the microbial load.